Negative regulation of cytochrome c-mediated oligomerization of Apaf-1 and activation of procaspase-9 by heat shock protein 90 - Pandey, Pramod (Oxford University Press, 2000)
The release of cytochrome c from mitochondria results in the formation of an Apaf-1–caspase-9 apoptosome and induces the apoptotic protease cascade by activation of procaspase-3. The present studies demonstrate that heat shock protein 90 (Hsp90) forms a cytosolic complex with Apaf-1 and thereby inhibits the formation of the active complex. Immunodepletion of Hsp90 depletes Apaf-1 and thereby inhibits cytochrome c-mediated activation of caspase-9. Addition of purified Apaf-1 to Hsp90-depleted cytosolic extracts restores cytochrome c-mediated activation of procaspase-9. We also show that Hsp90 inhibits cytochrome c-mediated oligomerization of Apaf-1 and thereby activation of procaspase-9. Furthermore, treatment of cells with diverse DNA-damaging agents dissociates the Hsp90–Apaf-1 complex and relieves the inhibition of procaspase-9 activation. These findings provide the first evidence for a negative cytosolic regulator of cytochrome c-dependent apoptosis and for involvement of a chaperone in the caspase cascade.